A cluster randomised controlled trial of an intervention based on the Health Action Process Approach for increasing fruit and vegetable consumption in Iranian adolescents. Issue 12 (2nd December 2017) - Lin, Chung-Ying; Scheerman, Janneke F.M.; Yaseri, Mehdi; Pakpour, Amir H.; Webb, Thomas L.
Abstract : Objective: To evaluate an intervention programme based on the Health Action Process Approach and designed to increase the intake of fruit and vegetables (F&V) among Iranian adolescents aged 13 to 18. Design: A randomised controlled trial with three arms examined the short- (1 month) and long-term (6 months) effects of the intervention. There were two intervention groups (one included adolescents only [A group; n  = 510]; the second included mothers and adolescents [M + A group; n  = 462]) and a control group ( n  = 483). All participants were recruited from schools. Main outcome measures: Social cognitions, self-regulatory processes and F&V intake. Results: The intervention led to an increase in F&V intake for adolescents in the short and long terms. Adolescents in the M + A group increased their F& V intake more than adolescents in the A group. Outcome expectancies, self-monitoring, intentions, action and coping planning, perceived social support and behavioural automaticity mediated the effect of the intervention on F&V intake. Conclusion: The theory-based intervention led to an increase in F&V intake and promoted more positive social cognitions and self-regulatory processes among Iranian adolescents. The findings also provide evidence that involving mothers in an intervention can confer additional benefit.